Analysis of risk factors associated with central neuropathy in patients with primary Sjögren's syndrome - Chao YUAN; Jiaman ZHENG; Lijuan ZHENG; Renge LIANG; Jiayi LIU; Qin HUANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2021)
Objective: To explore the clinical manifestations and risk factors of primary Sjögren's syndrome associated central nervous system (pSS-CNS). Methods: A total of 291 patients with primary Sjögren's syndrome (pSS) in Nanfang Hospital of Southern Medical University from January 2015 to December 2020 were selected and divided into the pSS-CNS group and pSS-non-CNS group.The general conditions, laboratory data were collected to analyze the clinical characteristics between the two groups. Then multivariate Logistic regression analysis was performed on the risk factors of pSS-CNS, and ROC curve was drawn to evaluate the predictive value of each risk factor. Results: ① pSS-CNS patients were mainly neuromyelitis optic spectrum disorders (NMOSD, 15 cases, 33.3%), the other 30 cases included leukoaraiosis, stroke, epilepsy, dementia and other central lesions. ② pSS-CNS group had a higher European League Against Rheumatism Sjögren's Syndrome Disease Activity Index (ESSDAI) than pSS-nCNS group [(11.14±2.97) vs (5.39±2.06), P<0.01]. ③ The independent risk factors for pSS-CNS were IgG (OR: 0.890; 95% CI: 0.826~0.959; P=0.002), IgM (OR: 0.367; 95% CI: 0.182~0.739; P=0.005), CH50 (OR: 0.935; 95% CI: 0.901~0.970; P<0.01), PLT (OR: 1.005; 95% CI: 1.001~1.009; P=0.010), the following curves of the four area: 0.890(0.826~0.959), 0.367 (0.182~0.739), 0.935(0.901~0.970), 1.005(1.001~1.009), and the area under the curve of the combined application of the four was 0.790 (0.761~0.858). Conclusions: The clinical manifestations of pSS-CNS are varied. Some patients may present the symptoms of central nervous system as their first or only clinical symptom. In our study, NMOSD was the most common one. IgG, IgM, CH50 and PLT are independent risk factors for pSS-CNS, among which, the higher the PLT, the lower the IgG, IgM and CH50, and the higher the possibility of central neuropathy.